2016
DOI: 10.1530/rep-15-0419
|View full text |Cite
|
Sign up to set email alerts
|

The effects of voluntary exercise on oocyte quality in a diet-induced obese murine model

Abstract: Obesity negatively affects many aspects of the human body, including reproductive function. In females, the root of the decline in fertility is linked to problems in the oocyte. Problems seen in oocytes that positively correlate with increasing BMI include changes to the metabolism, lipid accumulation, meiosis, and metaphase II (MII) spindle structure. Studies in mice indicate dietary interventions fail to reverse these problems [4]. How exercise affects the oocytes has not been addressed. Therefore, we hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 45 publications
(62 reference statements)
3
39
0
Order By: Relevance
“…Four-week-old female C57Bl/6 mice were fed either a high-fat/ high-sugar (HF/HS) (Test Diet 58R3; 59% fat, 26% carbohydrates [17% sucrose] and 15% protein) or standard chow (Con) (PicoLab Rodent diet 20; 13% fat, 62% carbohydrates [3.2% sucrose] and 25% protein for six weeks (Boudoures et al, 2016; Reynolds et al, 2015). Con- and HF/HS-fed F0 mice were mated with chow-fed male mice to produce the first generation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four-week-old female C57Bl/6 mice were fed either a high-fat/ high-sugar (HF/HS) (Test Diet 58R3; 59% fat, 26% carbohydrates [17% sucrose] and 15% protein) or standard chow (Con) (PicoLab Rodent diet 20; 13% fat, 62% carbohydrates [3.2% sucrose] and 25% protein for six weeks (Boudoures et al, 2016; Reynolds et al, 2015). Con- and HF/HS-fed F0 mice were mated with chow-fed male mice to produce the first generation.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, we demonstrated that female mice with diet-induced metabolic syndrome had abnormal oocyte mitochondrial morphology characterized by fewer, more disarrayed cristae, decreased electron density of the matrix, increased swelling, and more vacuoles (Luzzo et al, 2012). Additionally, oocyte mitochondria from mice fed a high fat-high sugar (HF/HS) were less round and more dumbbell shaped than their chow-fed counterparts, suggesting a defect in mitochondrial dynamics (Boudoures et al, 2016). These defects in mitochondrial morphology were accompanied by impaired beta oxidation (Boudoures et al, 2016), decreased mitochondrial membrane potential (Reynolds et al, 2015), and altered ATP and citrate levels (Boudoures et al, 2016; Luzzo et al, 2012; Reynolds et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, obese mice experience infertility and one mechanism is that oocyte development is impeded resulting in aberrant spindle formation. Reversal of the obesity by diet alone or by exercise does not eliminate the spindle disorders (Reynolds et al, 2015;Boudoures et al, 2016). The mechanism of obesity-related oocyte damage is not fully elucidated and may involve oxidative damage and abnormal lipid accumulation in the oocyte.…”
Section: A Major Effect Of Uterine Disease Is Subsequent Failure Of Fmentioning
confidence: 99%
“…Weight loss, at least in mice, did not show reversal of these negative defects or reverse oocyte lipid accumulation, alterations in TCA cycle metabolite levels and mitochondrial membrane potential, or abnormalities in mitochondrial distribution, despite reversal of the metabolic phenotypes of obesity (Reynolds et al 2015). But effects can be reversed with therapies specifically targeting the mitochondrial respiratory chain (Boots et al 2016) or ER stress, and oocyte competence has been improved with voluntary exercise regimes (Boudoures et al 2016). These impairments in oocytes are associated with poor blastocyst and embryo development, increased ROS production as well as mitochondrial dysfunction in embryos (Igosheva et al 2010, Wu et al 2010, Boudoures et al 2017.…”
Section: Journal Of Endocrinologymentioning
confidence: 98%